Effects of Akt/mTOR/p70S6K Signaling Pathway Regulation on Neuron Remodeling Caused by Translocation Repair - Yuan, Yusong; Li, Dongdong; Yu, Fei; Kang, Xuejing; Xu, Hailin; Zhang, Peixun (Frontiers in Neuroscience, 2020)
Peripheral nerve injury repair has been considered a difficult problem in the field of trauma for a long time. Conventional surgical methods are not applicable in some special types of nerve injury, prompting scholars to seek to develop more effective nerve translocation repair technologies. The purpose of this study was to explore the functional state of neurons in injured lower limbs after translocation repair, with a view to preliminarily clarify the molecular mechanisms underlying this process. Eighteen Sprague–Dawley rats were divided into the normal, tibial nerve in situ repair, and common peroneal nerve transposition repair tibial nerve groups. Nerve function assessment and immunohistochemical staining of neurofilament 200 (NF-200), protein kinase B (Akt), mammalian target of rapamycin (mTOR), and ribosomal protein S6 kinase (p70S6K) in dorsal root ganglia were performed at 12 weeks after surgery. Tibial nerve function and neuroelectrophysiological analysis, osmic acid staining, muscle strength testing, and muscle fiber staining showed that nerve translocation repair could restore the function of the recipient nerve to a certain extent; however, the repair was not as efficient as the in situ repair. Immunohistochemical staining showed that translocation repair resulted in changes in the microstructure of neuronal cell bodies, and the expressions of Akt, mTOR, and p70S6K in the three dorsal root ganglia groups were significantly different (p <0.05). This study demonstrates that nerve translocation repair technology sets up a new reflex loop, with the corresponding neuroskeletal adjustments, in which donor neurons dominate the recipient nerves. This indicates that nerve translocation repair technology can lead to neuronal remodeling and is important as a supplementary treatment for peripheral nerve injury. Furthermore, the Akt/mTOR/p70S6K signaling pathway may be involved in the formation of the new neural reflex loop created as a result of translocation repair.